Synergistic effect of humic acid on alkali pretreatment of sugarcane bagasse for the recovery of lignin with phenomenal properties. (March 2020) - Uma Maheswari, R.; Mavukkandy, Musthafa O.; Adhikari, Utpal; Naddeo, Vincenzo; Sikder, Jaya; Arafat, Hassan A.
Abstract: Lignin forms a recalcitrant structure in lignocellulosic biomass and hence huge amount of enzymes are required for disintegrating it into their subsequent components, like glucose and other by-products. Thus, the pretreatment is an ineluctable step in the bioethanol scheme for the delignification of biomass and also the recovery of lignin, an emerging value added polymer in many industrial applications. A green facile method was developed wherein humic acid (HA) acts as a catalyst and surfactant in the alkali pretreatment of sugarcane bagasse for the step reduction in lignin recovery scheme with phenomenal properties and enhanced enzymatic-hydrolysis. HA assisted experiments were performed with and without calcium chloride (CaCl2 ). Effective disintegration of lignocellulose by the cleavage of β-O-4 moieties resulted in forming lignin and hydrolyzable biomaterial via two pathways. Possible covalent linkages between the HA and lignin resulted in the release of esters as a byproduct. Thus, the delignified biomass, the isolated lignin and a variety of esters, could be valorised in various industrial applications. The biomass was characterized by XRD and SEM analysis. The isolated lignin was characterized using FTIR, NMR, GPC, SEM, and TGA – DTA studies. The yield of recovered pure lignin for the two process was 90–100%, as measured through gravimetric analysis. The produced esters were confirmed using FTIR studies. Batch enzymatic hydrolysis was performed for the HA assisted de-lignified bagasse (without CaCl2 ), which demonstrated a 19% increase in glucose yield compared to the alkali treated bagasse. The produced hydrolysates were subjected to fermentation for the production of ethanol. Highlights: A humic acid‒alkali based protocol was developed for fractionation of lignocellulose. Humic acid helps bypass multiple filtrations, centrifugation and precipitation steps. Isolated lignin showed unusual properties such as varied weight distributions. Humic acid‒assisted protocol also achieved an increase in the glucose yield. A novel pretreatment scheme is proposed for the better circular economy.